Spatial indices and SDG indicator-based urban environmental change detection of the major cities in Bangladesh - Sumya Tasnim; Farzana Mahbub; Gopa Biswas; Dewan Mohammad Enamul Haque (Journal of Urban Management, 2022)
Understanding a city's urban growth trend and associated environmental change scenarios is necessary to ensure the quality of life of urban people by sustaining ecosystem health. We have performed urban environmental change detection for the major cities in Bangladesh based on the analysis of urban indices using remote sensing techniques. We have further correlated these indices-derived outcomes with Sustainable Development Goal (SDG) number 11 (sustainable cities and communities) by estimating the SDG indicator 11.3.1. This indicator deals with the urban land consumption rate ratio to the population growth rate. We calculated the Impervious Surface Area (ISA), Vegetation Fraction (VF), and Biotope Area Ratio (BAR) for Dhaka, Chittagong, Sylhet, and Khulna-the four major cities in Bangladesh. We have also estimated the Normalized Urban Area Composite Index (NAUCI) as NAUCI utilizes further information from other pertinent pre-established indices like NDVI, NDWI, and NDBI. These widely used indices are also essential to consider because these indicators are also directly related to land consumption and population growth. Here we find that each of the considered cities is expanding significantly faster. Therefore, the ecology of the urban environment is degrading as well as the cities' conditions are worsening in terms of SDG 11.3.1. Dhaka, Chittagong, and Sylhet exhibit a lowering trend of the SDG indicator, whereas Khulna city show the opposite; however, we found Khulna's urban growth like the other cities under investigation is harming the ecology too.
Keywords: 710